Análise estratigráfica e geoquímica através de isótopos de enxofre em sequências pelíticas e mistas na formação Morro do Chaves da Bacia Sergipe-Alagoas - Pontes, Naedja Vasconcelos (2013)
Morro do Chaves Formation are considered important potential hydrocarbons source rock of the Sergipe-Alagoas basin. Cretaceous shales from Morro do Chaves Formation have been investigated to identify their isotopic signature and source areas by stable sulphur ä34S isotopes technique. In addition, this study shows the potential source rocks based on organic geochemical parameters. The 16 samples of shales were collected and submitted to total organic carbon (TOC), total sulphur (S), Rock-Eval pyrolysis and stable sulphur isotopes ä34S. The TOC and Rock Eval results revealed high organic contents and the predominance of kerogen classified as type I. The results of the geochemical analyses indicated TOC and S contents reaching 9,22% and 1,67%, respectively and it was possible to observe two intervals anoxic events. The results indicate sea water source from the bacterial sulfate reduction to high values of the sulfur isotopic ratio and low values reflect the isotopic signature of meteoric water. The paleoenvironment conditions were characterized like lagoon ambient with possibility marine invasion.